SUSTAINABLE MARKETING CONCEPT - Tosun, Petek (Journal of Strategic Innovation and Sustainability, 2017)
Marketing is criticized to be inherently controversial to sustainability because of boosting sales in the pursuit of profits. However, it is generally overlooked that marketing theory and practice can support sustainability. The consumption dilemma between the short-term outcomes such as achieving profits and the long-term societal outcomes such as protecting the environment may subsist; on the other hand, a collaboration obtained among the marketers, firms, regulators and the society can support sustainability. This article reviews the literature regarding the sustainability aiming to clarify the related concepts and integrate them with the theoretical and practical perspectives of marketing.